Pembuatan Alat Tanam Padi Manual 4 Alur Model IRRI (International Rice Research Institute) - Elok Kurnia Novita Sari; Supriyono; Dimas Jaya Abadi; Annisa Yunia Maulidia (Jurnal Teknik Pertanian Terapan, 2023)
A modified 4-groove manual rice planting tool from the IRRI (International Rice Research Institute) paddy transplanter aims to reduce dimensions and weight without changing its original function. The main components of this rice planting tool are frame, hopper, dispensing hole, skateboard, transplanting arm and picker arm. Materials for tool construction include iron plates, iron axles, bicycle chain sprockets, and light wood boards. This rice planting tool weighs 20.05kg, the planting distance between rows is 21 cm, the average planting depth is 4.5 cm. The prototype of the IRRI model 4-groove manual rice planting tool has been tested for performance and obtained an average theoretical field capacity of 0.0683 ha / hour. With a field speed of 0.226 m/s, the average effective field capacity is 0.0440 ha/hour, the average field efficiency is 64.44%, the number of empty holes (missing hills) is on average 4.7%, the number of lying plants is on average 6.3%, the uniformity of planting seedlings is on average 88.3% and the slope of plants is obtained on average 85°. This 4-groove manual rice planting tool is easy to make with materials that are easily available at affordable prices for farmers.